Structural and photoluminescence properties of Eu3+-activated BaTiO3 phosphors - Priya R.; Sharma P.; Kumar D.; Smriti; Pandey O.P. (My University, 2025)
Herein, we have reported the facile synthesis of phase pure and crystalline Eu doped BaTiO3 phosphors via solid-state method. The concentration of the Eu3+ ions in BaTiO3 is varied from 1 to 5 mol%. The structural, morphological and optical properties are characterized by X-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM), UV-Visible and photoluminescence (PL) technique, respectively. The structural parameters are further determined by using Rietveld refinement. The excitation spectra revealed that synthesized samples can be excited by near UV (396 nm) and visible blue light (465 nm) and the highest emission intensity is observed at 617 nm under 465 nm excitation, corresponding to the 5D0–7F2 transition of Eu3+ ions. The photoluminescent properties are studied via applying Dexter and Blasse's theory and CIE coordinates are calculated. The decay curves exhibited bi-exponential behavior for all the samples and lifetimes values varied from 0.409 to 0.320 msec, for 1 to 5 mol% Eu doped BaTiO3 phosphors. The obtained results indicate that synthesized samples have potential applications in optoelectronic and display devices. © 2021